ANALISIS KINERJA KEUANGAN PT. UNITED TRACTOR TBK - -, Ilaika Lafiari (EKONOMIA, 2019)
The theoretical basis of this research is financial management that focuses on financial ratios. The analytical tool used is liquidity ratio, Solvability ratio, Profitability and Growth ratios. The results of the analysis and discussion show that the liquidity growth from the Current Ratio aspect has decreased for 3 years, namely in 2012 by -4%, in 2013 by -25%, and in 2014 by -9%. 2015 experienced a growth of 2% and 2016 of 3%. Cash Ratiom experienced growth from 2012 by -40% to 68% in 2013. In 2014, 27% grew to 28% in 2015, and 2016 decreased by 7%. Debt to Asset Ratio grew from -35% in 2012 to 45% in 2013. In 2014, 6% grew to 15% in 2015. 2016 decreased by 3%. Debt To Equity Ratio experienced growth in 2012 of -45% to 64% in 2013. 2014 decreased by 13% and 2015 grew by 21%. 2016 decreased by 6%. In 2012 Return on Investment amounted to 6%, decreased for 3 years, namely 2013 by -39%, 2014 by -9% and 2015 by -40%. 2016 experienced a growth of 67%. Return on Equity decreased for 4 years, namely in 2012 amounted to -10%, in 2013 amounted to -21%, in 2014 amounted to -7%, in 2015 at -29% and experienced growth in 2016 of 60%. Based on the results of the analysis show that there is growth and decline (fluctuations) in financial performance both in the previous year and after, namely from 2012-2016. Thus the hypothesis is rejected or unacceptable